Brucella pericarditis: A forgotten cause of chest pain - Feridoun Sabzi; Reza Faraji (Babol University of Medical Sciences, 2017)
Background: Brucellosis pericarditis is an extremely rare involvement of the cardiovascular system with Brucella species that has worldwide distribution and is endemic in many provinces of Iran. Case presentation: The present report describes an exceptional case of pericardial involvement by Brucella melitensis in a 50- year-old woman. The patient presented with night sweats, mild fever, weight loss, and chest pain. Conclusion: Pericarditis occurs during the course of brucellosis as an isolated cardiac symptom and may be   asymptomatic or may be manifested with chest pain as ischemic heart disease.